Peran Program Rancang Bangun Wadah Cuci Tangan dalam Meningkatkan Kesadaran Higiene dan Proteksi terhadap Pandemi Covid-19 di Desa Kute Bakti, Aceh Tenggara - Arhami, Arhami; Masri, Masri; Husaini, Husaini; Suhaeri, Suhaeri; Thaib, Anwar (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2023)
The problem of the Corona Virus Disease 2019 (COVID-19) started at the end of 2019 when it first appeared in Wuhan, China. It was reported that by July 2020, COVID-19 had become a pandemic that spread to 193 countries, including Indonesia. Although the severe outbreak of the COVID-19 pandemic has started to subside over time, it is important to acknowledge that another pandemic might occur. This paper aims to contribute to the efforts of preventing and controlling the COVID-19 pandemic outbreak by implementing health protocols. The health protocol in question includes three important measures: handwashing, mask-wearing, and avoiding crowds, collectively known as the "3M" protocol. The COVID-19 thematic community service activities are conducted in Kute Bakti village, Babul Makmur District, Southeast Aceh Regency, Aceh Province. This location was chosen as it serves as a gateway for people traveling between provinces and is situated on the southeastern border between Aceh and North Sumatra provinces. The community service program that has been implemented consists of two programs: the design of handwashing containers for use outside residents' homes and an outreach program focusing on health protocols. This community service program aims to assist the community in preventing and protecting against the impact of the COVID-19 pandemic's spread, both in Aceh province overall and specifically in Kute Bakti village, Southeast Aceh district.